Functional white chocolate enriched with cold-pressed sea buckthorn (Hippophae rhamnoides L.) oil as a partial cocoa butter replacer - Slavik Dadayan; Artavazd Poghosyan; Lilit Arstamyan; Ani Chakhoyan; Anahit Hovhannisyan; Narine Hovhannisyan; Nune Simonyan; Gayane Aperyan; Ani Dadayan (Functional Foods in Health and Disease, 2026)
Background: The ever-growing demand for functional and organic foods has stimulated interest in natural, environmentally friendly raw materials rich in bioactive compounds. Sea buckthorn (Hippophae rhamnoides L.) berries contain a wide range of lipophilic bioactive compounds, including carotenoids, tocopherols, vitamins, and essential mineral elements, which have been associated with antioxidant activity and other beneficial physiological effects. The oil obtained from sea buckthorn berries by cold pressing is particularly attractive due to the preservation of their native form and biological activity. At the same time, considerable attention is being paid to the development of alternative lipid sources for chocolate production, particularly with a view to partially replacing cocoa butter. The incorporation of non-traditional vegetable oils into chocolate formulations represents a promising approach to improving the nutritional profile whilst maintaining the desired technological and organoleptic characteristics. White chocolate, thanks to its specific lipid matrix, offers a suitable system for incorporating beneficial oils and developing novel confectionery products. Objective: This study aimed to produce sea buckthorn oil via cold pressing from raw materials cultivated in Armenia, to evaluate its elemental composition, fatty acid profile, and essential quality indicators, as well as to investigate its application in various concentrations for the production of functional white chocolate with partial cocoa butter replacement. Methods: Sea buckthorn oil was obtained by cold pressing and comprehensively characterized prior to its incorporation into the chocolate formulations. Elemental analysis was carried out by ICP-OES, while the fatty acid profile was determined by gas chromatography with flame ionization detection (GC–FID). The oil was further evaluated by measuring its organoleptic characteristics together with the principal physicochemical quality parameters, including refractive index, iodine value, peroxide value, acid value, and saponification value, following established analytical methods. White chocolate samples containing different levels of sea buckthorn oil as a partial cocoa butter replacer were prepared and subsequently evaluated through sensory assessment. Results: The oil contained nutritionally relevant mineral elements, with calcium (31.44 ppm) and magnesium (13.28 ppm) present at the highest concentrations, while arsenic, cadmium, and lead were not detected. Among the peaks assigned using the available reference standards, the C18:1 methyl ester fraction showed the highest relative peak area (37.47%), followed by C16:0 methyl ester (22.41%). Several additional chromatographic peaks remained unidentified because peak assignment was based on a limited set of fatty acid methyl ester reference standards. Among the tested formulations, the sample containing 10% sea buckthorn oil showed the highest observed sensory preference and was therefore selected as the preferred formulation. Novelty: This study combines the characterization of Armenian cold-pressed sea buckthorn oil with its application as a partial cocoa butter replacer in white chocolate sweetened with natural honey. The combination of analytical characterization, product formulation, and sensory evaluation allowed the selection of a clean-label formulation enriched with naturally derived functional ingredients while maintaining desirable sensory properties. The principal scientific contribution of the study is the demonstration of the feasibility of incorporating characterized Armenian cold-pressed sea buckthorn oil into white chocolate as a partial cocoa butter replacer, with the 10% formulation showing the highest observed sensory preference among the tested formulations. Conclusion: The results showed that cold-pressed sea buckthorn oil can be incorporated into white chocolate as a partial replacement for cocoa butter. The formulation containing 10% sea buckthorn oil was the most preferred during sensory evaluation, indicating that this ingredient may be used to develop white chocolate formulations incorporating naturally derived ingredients and bioactive lipid components. Keywords: sea buckthorn oil, cold pressing, functional white chocolate, cocoa butter replacement, fatty acid composition, elemental analysis.